The evolving role of agriculture in climate change negotiations: Progress and players - Kalfagianni A; Duyck, S. (2015)
This paper documents and analyzes the substantive and discursive progress regarding agriculture as a discussion item in climate change negotiations. Our analysis traces agriculture’s negotiating history from the establishment of the United Nations Framework Convention on Climate Change in 1992 until the 20th Conference of the Parties in Lima in December 2014. We find that while agriculture has progressed into an important theme in the negotiations, albeit with shifting discourses, explicit commitments on agriculture have not materialized yet. We explain progress using three analytical lenses: (a) the position of key states in the negotiations; (b) the particularities of agriculture as a political issue; and (c) the role of non-state actors in the negotiation process. Our analysis relies on an extensive review of the scientific literature and policy documents and 16 semi-structured interviews with climate change negotiators and representatives from relevant observer organizations involved with agriculture.